5‐HTTLPR differentially predicts brain network responses to emotional faces. Issue 7 (30th April 2015) - Fisher, Patrick M.; Grady, Cheryl L.; Madsen, Martin K.; Strother, Stephen C.; Knudsen, Gitte M.
Abstract The effects of the 5‐HTTLPR polymorphism on neural responses to emotionally salient faces have been studied extensively, focusing on amygdala reactivity and amygdala‐prefrontal interactions. Despite compelling evidence that emotional face paradigms engage a distributed network of brain regions involved in emotion, cognitive and visual processing, less is known about 5‐HTTLPR effects on broader network responses. To address this, we evaluated 5‐HTTLPR differences in the whole‐brain response to an emotional faces paradigm including neutral, angry and fearful faces using functional magnetic resonance imaging in 76 healthy adults. We observed robust increased response to emotional faces in the amygdala, hippocampus, caudate, fusiform gyrus, superior temporal sulcus and lateral prefrontal and occipito‐parietal cortices. We observed dissociation between 5‐HTTLPR groups such that LALA individuals had increased response to only angry faces, relative to neutral ones, but S′ carriers had increased activity for both angry and fearful faces relative to neutral. Additionally, the response to angry faces was significantly greater in LALA individuals compared to S′ carriers and the response to fearful faces was significantly greater in S′ carriers compared to LALA individuals. These findings provide novel evidence for emotion‐specific 5‐HTTLPR effects on the response of a distributed set of brain regions including areas responsive to emotionally salient stimuli and critical components of the face‐processing network. These findings provide additional insight into neurobiological mechanisms through which 5‐HTTLPR genotype may affect personality and related risk for neuropsychiatric illness. Hum Brain Mapp 36:2842–2851, 2015. © 2015 Wiley Periodicals, Inc.